Research on the CSR Reporting Disclosure Practice in China – Critical Evaluate the Different Gap between the BP and CNPC - LI, Yihang (2009)
The corporate social responsibility (CSR) is becoming more and more important in today’s business, because the CSR shows the corporate culture, reputation and accountability to the public; so the CSR Reporting is the best way to disclose the corporate non-financial issues to the public. Nowadays, the CSR Reporting is still a new subject and the report’s purpose is not familiar to the users in China, only large enterprise publishes CSR reports every year and the report disclosure practice is still in a very poor situation. In this dissertation, I am going to investigate the CSR Reporting leading-edge disclosure practice and the report guidelines, in order to gain the different gaps between the leading-edge organization and Chinese organization’s disclosure practice. The BP and CNPC will recognize as the research cases in this dissertation.